The Influence Of Work Environment And Work Discipline On Employee Performance At The Pondok Aren District Office In South Tangerang - Aida, Vivi Nur; Nurdina, Anisa (Utami Publisher, 2025)
This study aims to determine the effect of work environment and work discipline on employee performance at the Pondok Aren District Office in South Tangerang. The research method used is a quantitative method with a data collection method using a questionnaire. The study population consisted of all 50 employees of the Pondok Aren District Office, the sampling technique used saturated samples, namely 50 people. The results of the study, based on the results of multiple linear regression tests with the equation value Y = 11.605 + 0.214 X1 + 0.574 X2 showed a positive correlation between work environment (X1) and work discipline (X2) on employee performance (Y), the results of the coefficient of determination test showed that work environment and work discipline contributed to employee performance by 0.695 or 69.5%, while 30.5% were factors not studied. The results of the t-test of the Work Environment variable (X1) had a positive and significant effect on employee performance with a t-value of 6.991> t-table 1.677 and a significance of 0.000 <0.05. The Work Discipline variable (X2) also has a positive and significant effect on employee performance with a calculated t value of 10.099 > t table 1.677 with a significance of 0.000 < 0.05. Based on the results of the F test with a calculated F value of 53.464 > F table 3.20 and a significance of 0.000 < 0.05, it can be concluded that simultaneously the work environment and work discipline have a significant effect on employee performance at the Pondok Aren District Office.